The virtues of leadership : contemporary challenges for global managers - Rego, Arménio (Oxford University Press, 2012)
In a globalized world, where multinational companies have extensive power over a huge number of other organizations and millions of people, building positive organizational performance requires global leaders with virtues. Organizations, especially multinational ones, may be crucial engines of social and economic progress; global leaders' virtues and character strengths may be strong drivers of such an endeavour. One cannot demand of them that they be morally pure or that theyassume responsibility for solving the most pressing public problems in the world. However, this book argues that they may be part of the solution, help in making the world a better place, and contribute to the realistic desiderata of a values-based capitalism. Drawing on the Positive Organizational Scholarship movement, this book aims to provide a holistic approach to the virtues of leaders. It explores how virtues and character strengths may be put at the service of positive organizational performance, stressing that virtues represent the 'golden mean' between the extremes of excess and deficiency, and discussing the perverse consequences of 'excessive virtuousness'. The book shares theoretical, anecdotal, and empirical evidence on the convergencebetween good virtues and good results, aiming to disseminate the idea that managers can be competent and competitive, whilst doing 'good things right'.